Vaginal hysterectomy in Primary Health Center, Darchula: A remote area of rural Nepal - Pant, Padam R; Joshi, Bhoj R; Yogi, Karbir N; Mishra, Shyam S; Tinkari, Bhim S (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To make situational analysis of getting organized with vaginal hysterectomy and pelvic floor repair for uterine prolapse in Primary Health Center in remote area. Method: This is a prospective descriptive study conducted in a three bedded Primary Health Center ‘Gokuleswar' of Darchula district in far western region of Nepal. The vaginal hysterectomy camp was funded by Ministry of health. Women with second and third degree prolapse or complete procidentia were screened for operation. Patient were investigated for urine routine and microscopic examination, blood grouping, haemoglobin, total and differential count, bleeding time clotting time, blood sugar random, HIV, HBsAg. Result: 72 patients were operated. Majority of the patients were 40-50 years of age. Two patients (2.7%) were below 30 years of age. Parity ranged from 2-13. Among the operated patients, 49 (68 %) had complete procidentia. More than half of the patient 37(51.38%) had prolonged bleeding time, one patient (1.38%) needed laprotomy for uncontrolled bleeding and required right sided internal artery ligation for haemostasis. Conclusion: Providing surgical service in rural setting at their own door step to the Nepalese women who have no time to travel to different hospital at their own cost is divine. Such an out reach programme is a major health benefit. Key words: Uterovaginal prolapse, vaginal hysterectomy, rural gynecological problem. doi:10.3126/njog.v2i1.1477 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 50 - 3 May -June 2007